AKT2 identified as a potential target of mir-29a-3p via microRNA profiling of patients with high proliferation lacrimal gland adenoid cystic carcinoma. (June 2022) - Zhao, Jinzhi; Liu, Xun; Lin, Jiaqi; Jiang, Meixia; Xu, Fei; Zhang, Chuanli; Tang, Qin; Zhu, Limin; Dong, Lijie; Lin, Tingting
Abstract: The lacrimal gland adenoid cystic carcinoma (LACC) is a major orbital malignancy. The recurrence rate and mortality rate are higher in high proliferation LACC(HP-LACC) compared with low proliferation LACC(LP-LACC). In this study, miRNA microarray was used to explore the differentially expressed miRNAs profiling between HP-LACC and LP-LACC and its potential signaling pathway. Tissues from 17 patients with LACC were collected and made into tissue microarrays. Patients were divided into a high proliferation group and a low proliferation group based on Ki-67 value. HE, immunofluorescence (IF), and Immunohistochemistry (IHC) were performed on the tissue microarrays. Eight LACC tissues(4 HP-LACC and 4 LP-LACC) were made into miRNA microarrays and analyzed for miRNA profiles. Differentially expressed miRNAs were analyzed by volcano plot and heat map. Target gene were predicted using the miRWalk and miRDB for these differentially expressed miRNAs, the intersection of the results are used as targets for further gene ontology and KEGG pathway analysis.The four differentially expressed miRNAs were validated by qRT-PCR, the miRNAs with statistically significant differences validated by dual luciferase reporter and qRT-PCR. Finally, IHC was used for their downstream signaling pathway proteins.HE staining showed the presence of tubular, cribriform, and basaloid structures in LACC. IF showed the presence of CK7, P63 fluorescence expression in all three structures.Patients were divided into HP-LACC and LP-LACC based on Ki-67 median value of 11%. IHC and survival analysis showed with the increase of KI-67 ratio, the proportion of P63 decreased, and the expression of P53 increased. The disease-free survival and overall survival of the patients decreased. IHC and survival analysis showed as Ki-67 expression increased, P63 expression decreased, P53 expression elevated, with prognosis worse. Heat map and volcano plot yielded 15 differentially expressed miRNAs between HP-LACC and LP-LACC.The 15 differential miRNAs were used to predict target genes in miRWalk and miRDB databases respectively, and there were 559 target genes after intersection.559 predicted target genes obtained. Go and KEGG analysis showed that these target genes exerted important biological functions through multiple signaling pathways. Among the 15 differentially expressed miRNAs, miR-29a-3p was verified to be significant by qRT-PCR. Dual luciferase reporter and tissue microarray immunohistochemical assays validated that AKT2 was a direct target gene of miR-29a-3p. Current studies have identified differentially expressed miRNAs associated with LACCs of variable proliferation ability, and found that AKT2 is a direct target gene of miR-29a-3p, which will contribute to target gene therapy in patients with high proliferation LACC in the future. Highlights: The division of HP-LACC and LP-LACC are based on both clinical features and histopathology appearences. MiR-29a-3p was firstly reported associated with HP-LACC. ATK2 was identified as a direct target of miR-29a-3p.